Brain metabolites in ISIAH and Wistar rats - O. B. Shevelev; A. A. Seryapina; A. L. Markel; M. P. Moshkin (Вавиловский журнал генетики и селекции)
Hypertension is one of the most common human diseases. This disease leads to serious disturbances such as myocardial infarction and stroke. Due to the development of nuclear magnetic resonance spectroscopy (NMRS), a decrease in neuron viability in different parts of the brain in humans with hypertension has been shown. Translation of NMRS tools to the clinic requires the accumulation of empirical data about neurometabolic changes in a strictly controlled experiment. It is particularly interesting to compare the metabolic parameters of laboratory animals with normal and high blood pressure kept in standard conditions on exactly the same diet. In this study, cortex and hypothalamus metabolites of ISIAH and Wistar male rats at the age of 8–9 weeks were examined. Cortex and hypothalamus metabolites were measured in animals under isoflurane anesthesia using proton magnetic resonance spectroscopy (1Н MRS). Processing of primary data using Partial least squares Discriminant Analysis (PLS-DA) allowed us to identify the main discriminating axis (Y1), its variations reflecting the predominance of excitatory neurometabolites (glutamine and glutamate) over inhibitory ones (GABA and glycine). In the cortex, the values of the Y1-axis were lower in ISIAH than in Wistar rats. This fact indicates a decrease in cortical excitability in hypertensive animals. By contrast, in the hypothalamus, the values of the Y1-axis were higher in ISIAH than in Wistar rats and the predominance of excitatory neurometabolites positively correlated with the level of mean blood pressure, which agrees well with the view of caudal hypothalamic activation in hypertensive animal models.